2012
DOI: 10.1080/01635581.2012.714832
|View full text |Cite
|
Sign up to set email alerts
|

DHA Effect on Chemotherapy-Induced Body Weight Loss: An Exploratory Study in a Rodent Model of Mammary Tumors

Abstract: Body weight loss during the course of cancer disease has been associated with poor prognosis. Beside cancer-associated cachexia, weight loss can also result from chemotherapy. This work explored whether a model of mammary tumors in female Sprague Dawley rats could be appropriate to study the effect of doxorubicin on body weight, described weight change in this model, and assessed the effect of DHA on weight during chemotherapy. After tumor induction, rats were randomly assigned to a control or a DHA-enriched d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
1
13
0
2
Order By: Relevance
“…In fact, knowledge on the treatment of muscle wasting is still at its infancy and additional confirmatory studies are needed, especially in cancer cachexia, which is further impaired by chemotherapy (Xue et al, 2011;Hajjaji et al, 2012;Garcia et al, 2013). Previous investigations showed that nutrition modulation using several nutrients (Xue et al, 2011;Hajjaji et al, 2012) and ghrelin (Garcia et al, 2013) may prevent body weight loss in cancer patients undergoing chemotherapy. Moreover, the metabolic modulator trimetazidine was also shown to activate protein synthesis signaling, while decreasing E3 ligase and myostatin levels in experimental models (Ferraro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, knowledge on the treatment of muscle wasting is still at its infancy and additional confirmatory studies are needed, especially in cancer cachexia, which is further impaired by chemotherapy (Xue et al, 2011;Hajjaji et al, 2012;Garcia et al, 2013). Previous investigations showed that nutrition modulation using several nutrients (Xue et al, 2011;Hajjaji et al, 2012) and ghrelin (Garcia et al, 2013) may prevent body weight loss in cancer patients undergoing chemotherapy. Moreover, the metabolic modulator trimetazidine was also shown to activate protein synthesis signaling, while decreasing E3 ligase and myostatin levels in experimental models (Ferraro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[48,49] Surprisingly, however, doxorubicin-induced cachexia was significantly dependent on the tumor TLR9-expression status. Several cytokines have been shown to mediate cachexia, including IL-8, TNF-α and MIC-1.…”
Section: Discussionmentioning
confidence: 99%
“…), dietary intake has also been shown to not be reduced in rats treated chronically with DOX (Hajjaji et al. ). Nonetheless, future studies are needed to discern the impact of changes in dietary‐intake on chemotherapy‐induced myotoxicity.…”
Section: Discussionmentioning
confidence: 99%